A STUDY ON CONSUMER PERCEPTION TOWARDS ELECTRIC VEHICLES IN BENGALURU CITY - L, Smitha (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The study’s goal was to investigate how consumers see electric cars (EVs) and assess the variables that affect their choice to buy one. The survey also sought to determine how Bengaluru city’s consumers felt about electric cars. Using a descriptive study design, a quantitative research approach was used. A questionnaire that was given to customers of E-vehicle users was used to gather data. Approximately 145 respondents made up the sample, which was chosen using convenience sampling methods. According to the study’s findings, consumer perceptions of factors like reducing air pollution and greenhouse gas emissions, gender, refuelling habits, the impact of government incentives and financial gains, curiosity, exposure to media sources and references, heterophily and serving as a source of information, affordability—both in terms of price and vehicle range—and design and style are all positively correlated with consumers’ propensity to purchase electric vehicles. Technological elements that positively correlate with consumers’ favourable perceptions of purchasing electric vehicles include disruptive innovation, advancements in battery technology, price premium reductions, superior e-vehicle service, low noise levels, operating costs, and energy independence through a decrease in oil imports.